Cordyceps collected from Bhutan, an appropriate alternative of Cordyceps sinensis - Wu, Ding-Tao (Sci Rep, 2016)
Natural Cordyceps collected in Bhutan has been widely used as natural Cordyceps sinensis, an official species of Cordyceps used as Chinese medicines, around the world in recent years. However, whether Cordyceps from Bhutan could be really used as natural C. sinensis remains unknown. Therefore, DNA sequence, bioactive components including nucleosides and polysaccharides in twelve batches of Cordyceps from Bhutan were firstly investigated, and compared with natural C. sinensis. Results showed that the fungus of Cordyceps from Bhutan was C. sinensis and the host insect belonged to Hepialidae sp. In addition, nucleosides and their bases such as guanine, guanosine, hypoxanthine, uridine, inosine, thymidine, adenine, and adenosine, as well as compositional monosaccharides, partial acid or enzymatic hydrolysates, molecular weights and contents of polysaccharides in Cordyceps from Bhutan were all similar to those of natural C. sinensis. All data suggest that Cordyceps from Bhutan is a rational alternative of natural C. sinensis, which is beneficial for the improvement of their performance in health and medicinal food areas.